2011
DOI: 10.1007/s10705-011-9431-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate loss via overland flow and interflow from a sloped farmland in the hilly area of purple soil, China

Abstract: Nitrate losses through runoff (both overland flow and interflow) represent a significant portion of the nitrogen (N) biogeochemical cycle. The mechanisms of this cycle have been well documented for flat agricultural lands. It is unclear, however, how nitrate loss takes place in sloping farmlands of purple soil. This paper reports the finding of a field experiment examining nitrate losses due to overland flow and interflow along sloping farmland sites dominated by a regosol known as purple soil in the Sichuan B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, the total amount of N leaching and runoff is generally very small because of the semiarid or arid climate, leading to a possible accumulation of NO 3 − in these ecosystems. By contrast, the azonal soils cannot retain mineral N under a humid climate, and both localized and widespread N pollution can occur (Huang et al ., ; Zhu et al ., ; Wang & Zhu, ; Zhang et al ., ). Therefore, zonal soils are characterized by soil properties such as a large N holding capability and efficient Nr cycling.…”
Section: Soil N Transformations Regulate the Form Of Mineral N Exportmentioning
confidence: 99%
“…However, the total amount of N leaching and runoff is generally very small because of the semiarid or arid climate, leading to a possible accumulation of NO 3 − in these ecosystems. By contrast, the azonal soils cannot retain mineral N under a humid climate, and both localized and widespread N pollution can occur (Huang et al ., ; Zhu et al ., ; Wang & Zhu, ; Zhang et al ., ). Therefore, zonal soils are characterized by soil properties such as a large N holding capability and efficient Nr cycling.…”
Section: Soil N Transformations Regulate the Form Of Mineral N Exportmentioning
confidence: 99%
“…This indicates that NO 3 – –N delivery occurs mainly via desorption processes and by a mixing with pre‐event water when overland flow moves across the soil surface, rather than from the sediments carried by the water. Wang and Zhu () also reported that nitrate loss through interflow is the main pathway of nitrate loss. Nevertheless, NO 3 – –N exhibited clockwise hysteresis (C1 type) in plot A 1 for the 13 August 2004 storm event.…”
Section: Discussionmentioning
confidence: 97%
“…In this initial period of infiltration, dissolved chemicals will move downward out of the mixing zone and are less available for transport by overland flow. Therefore, the loss of nitrate in surface runoff is often less than the amount lost to leaching pathways (Walter et al ., ; Wang and Zhu, ). Two‐phased pesticides and SRP move downward much more slowly than nitrate resulting in increased availability when runoff occurs and can be more readily mobilized in overland flow (Saia et al ., ).…”
Section: Conceptual Framework For Targeting Bmpsmentioning
confidence: 99%